2021
DOI: 10.3390/brainsci11060797
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and Nervous System Development and Function—New Findings 2015–2020

Abstract: Tobacco is a one of the most common addictive stimulants used by people around the world. The smoke generated during tobacco combustion is a toxic mixture of more than 5000 chemicals of which over 30 are known human carcinogens. While its negative effects on the human body are well understood, it remains a serious public health problem. One of the multiple effects of smoking is tobacco’s effect on the nervous system—its development and function. This review aims to summarize the progress made in research on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 69 publications
0
13
0
2
Order By: Relevance
“…Nicotine addiction is extensively employed as a stress reliever in today's contemporary lifestyle but longterm consumption may be hazardous for physical and mental health [32]. This may also affect brain activity, producing neurodegenerative illnesses and degrading the nervous system's potential [33]. In the survey, we observed that nicotine users often report that their consumption helps to relieve the feeling of stress, divert the way of thinking and improve work performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nicotine addiction is extensively employed as a stress reliever in today's contemporary lifestyle but longterm consumption may be hazardous for physical and mental health [32]. This may also affect brain activity, producing neurodegenerative illnesses and degrading the nervous system's potential [33]. In the survey, we observed that nicotine users often report that their consumption helps to relieve the feeling of stress, divert the way of thinking and improve work performance.…”
Section: Discussionmentioning
confidence: 97%
“…A questionnaire of 10 items based on the frequency of emotional feelings and thoughts during the past month was given to volunteers and asked them to respond. According to the overall individual's score, all volunteers were categorized into three stress categories as low stress (<13), moderate stress (14-26), and high stress (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) [30].…”
Section: Psychological Assessmentmentioning
confidence: 99%
“…In utero exposure and exposure of children to tobacco smoke are both believed to interfere with cognitive development, causing deleterious effects on attention span and ability to concentrate, in children ( Alhowail, 2021 ; Hajdusianek et al, 2021 ). With some caveats as to the strength of the evidence ( Chan et al, 2020 ) it is generally accepted that smoking in pregnancy is bad for the unborn child, although there is some doubt as to whether nicotine causes all of the problems noted ( Baler et al, 2008 ; Chan et al, 2020 ).…”
Section: Nicotinementioning
confidence: 99%
“…Tembakau dalam rokok juga merupakan salah satu faktor resiko penyebab datangnya penyakit pada tubuh, misalnya pada perubahan morfologis sistem saraf. Selain itu, asap tembakau mengandung lebih dari 7000 bahan kimia dengan lebih dari 4500 racun, dimana racun tersebut dapat mempengaruhi volume otak (Hajdusianek, Zorawik, Waliszewska-Prosol, Poreba, & Gac, 2021). Sekitar 15% asap rokok diserap oleh perokok dan 85% lainnya dilepaskan ke atmosfer.…”
Section: Pendahuluanunclassified